Análise de desempenho dos fundos de investimento em ações brasileiros no período de Janeiro de 1997 a outubro de 2006 - Egea, Fernando Galvão (2008)
This research evaluated the quality of the management of Brazilian stock funds on the period from January 1997 to October 2006. The analysis was based on the Modern Portfolio Theory measures of performance. In addition, this research evaluated the relevance of the performance measures The sample with 21 funds was extracted from the 126 largest Brasilian stock options funds because they were the only with quotas on the whole period. The monthly mean rate of return and the following indexes were calculated: total return, mean monthly return, Jensen Index, Treynor Index, Sharpe Index, Sortino Index, Market Timing and the Mean Quadratic Error. The initial analysis showed that the funds in the sample had different objectives and limitations. To make valuable comparisons, the ANBID (National Association of Investment Banks) categories were used to classify the funds. The measured results were ranked. The positions of the funds on the rankings based on the mean monthly return and the indexes of Jensen, Treynor, Sortino and Sharpe were similar. All of the ten ACTIVE funds of this research were above the benchmark (IBOVESPA index) in the measures above. Based on the CAPM, the managers of these funds got superior performance because they might have compiled the available information in a superior way. The six funds belonging to the ANBID classification of INDEXED got the first six positions in the ranking based on the Mean Quadratic Error. None of the researched funds have shown market timing skills to move the beta of their portfolios in the right direction to take the benefit of the market movements, at the significance level of 5%.